On the global solar radiation climate and evapotranspiration estimates in India (MAUSAM, 1970)
Constants a and b are worked out utilizing the available data for 17 radiation stations in India for estimating the average monthly global radi9tion (Qs) received at any low elevation station in India from the average monthly solar radiation received outside the atmosphere (QA) and the actual hours of bright sunshine (n) at the station, using the relation Qs=QA [a+b (n/N)] where LV =possible hours of bright sunshine. It is suggested that partitioning the Radiation Network by Thiessen's mean method, use can be made of these constants to form estimates of global radiation for any place in India, which compare well with the average global radiation estimates formed from the clear day radiation values and hours of bright sunshine. The importance of global radiation in estimating the pan evaporation from meteorological factors is discussed and computations of the monthly values of pan evaporation for 9 stations located in different Agroclimatic Zones of India for one year are presented to demonstrate the practical applicability of the method suggested for estimating the Qs values for our country.